Shared earth modeling : knowledge driven solutions for building and managing subsurface 3D geological models - Perrin, Michel, 1941 February 15-; Perrin, Michel, 1941 February 15-; Rainaud, Jean-François; Rainaud, Jean-François (Editions Technip, 2013)
Over the last two decades, earth modeling has become a major investigative tool for evaluating the potential of hydrocarbon reservoirs. Current modeling procedures provide no way to link a range of data and interpretations with a final earth model, and sharing and exchanging information about the model building process is at present a major difficulty. Recently, the term Shared Earth Modeling has been used to express the idea that earth models should be built so that experts and end users can have access to all the information incorporated into the model. This information not only concerns the data, but also the knowledge that geoscientists produce by interpreting these data. Accordingly, practical solutions must be studied to determine a way to operate a knowledge-driven approach to Shared Earth Modeling, which is the goal of this book. Relying on recent progress in various fields of computer science, the authors present innovative solutions for solving the critical issue of knowledge exchange at key steps of the modeling process.
Keywords: Geology -- Computer simulation.; Three-dimensional display systems.; elektronické knihy; electronic books